Effects of processing parameters on 3D structural ordering and optical properties of inverse opal photonic crystals produced by atomic layer deposition. Issue 2 (13th July 2019) - Campos, Heloisa G.; Furlan, Kaline P.; Garcia, Daniel E.; Blick, Robert; Zierold, Robert; Eich, Manfred; Hotza, Dachamir; Janssen, Rolf
Abstract: Vertical convective self‐assembly has been extensively used for the preparation of direct photonic crystals, which can be later infiltrated with a more stable material, such as oxide ceramics, by atomic layer deposition. However, the relationship between the self‐assembly parameters of the direct photonic crystals and the optical properties of the inverse opal photonic crystals remains elusive. In this work, the effect of different experimental parameters on the 3D structure and the density of defects of polystyrene direct photonic crystals produced by vertical convective self‐assembly was assessed. Self‐assembly was investigated using deionized water as media with polymer particles' concentrations up to 2 mg/mL; temperatures of 40, 50, and 80°C; and relative humidity of 45%, 70%, and 90%. The 3D structure of the resultant direct photonic materials was characterized by the combination of scanning electron microscopy and image analysis, and their optical properties were assessed by reflectance measurements. These results were correlated with the performance of oxide‐based inverse opal photonic crystals produced by the controlled infiltration of the former direct photonic crystals by atomic layer deposition (ALD). It was found that the thickness increased with the concentration of polystyrene particles, while the photonic structure ordering is dependent on the synergy between humidity and temperature. Results also showed higher defects population with increasing evaporation temperature and decreasing relative humidity. Abstract : In the present paper, the effect of processing parameters during vertical convective self‐assembly of PS spheres is investigated concerning structure and stability of alumina‐based inverse opal photonic crystals. The results show that the process of template synthesis is an essential aspect regarding the final performance of the desired photonic materials.